Transesterification/Esterification Of Non-Edible And Waste Cooking Oils To Fame And Glycerol Free Fame Using Carbon And Silica-Based Catalysts - Chin, Lip Han (2014)

(untitled)
Biodiesel, also known as fatty acid methyl esters (FAME), is an alternative fuel for diesel engines that is gathering attention worldwide. However, the burden of excess low-value glycerol by-product that is produced in traditional transesterification may thwart the growth of the biodiesel industry. Therefore, this study aims to investigate the feasibility of two processes (two-step and single-step) to produce glycerol-free FAME. Biodiesel, juga dikenali sebagai asid lemak metil ester (FAME), adalah bahan api pengganti untuk enjin diesel yang sedang mendapat perhatian di seluruh dunia. Walau bagaimanapun, tanggungan daripada produk hasil sampingan gliserol bernilai rendah yang dihasilkan berlebihan dalam transesterifikasi lama boleh menggagalkan perkembangan industri biodiesel. Oleh itu, kajian ini bertujuan untuk mengkaji keberkesanan dua proses (dua-langkah dan langkah-tunggal) untuk menghasilkan “FAME” bebas gliserol.